TGFβ (Transforming Growth Factor-Beta)–Activated Kinase 1 Regulates Arteriovenous Fistula Maturation. Issue 7 (July 2020) - Hu, Haidi; Lee, Shin-Rong; Bai, Hualong; Guo, Jianming; Hashimoto, Takuya; Isaji, Toshihiko; Guo, Xiangjiang; Wang, Tun; Wolf, Katharine; Liu, Shirley; Ono, Shun; Yatsula, Bogdan; et al.
Abstract : Objective: Arteriovenous fistulae (AVF) are the optimal conduit for hemodialysis access but have high rates of primary maturation failure. Successful AVF maturation requires wall thickening with deposition of ECM (extracellular matrix) including collagen and fibronectin, as well as lumen dilation. TAK1 (TGFβ [transforming growth factor-beta]–activated kinase 1) is a mediator of noncanonical TGFβ signaling and plays crucial roles in regulation of ECM production and deposition; therefore, we hypothesized that TAK1 regulates wall thickening and lumen dilation during AVF maturation. Approach and Results: In both human and mouse AVF, immunoreactivity of TAK1, JNK (c-Jun N-terminal kinase), p38, collagen 1, and fibronectin was significantly increased compared with control veins. Manipulation of TAK1 in vivo altered AVF wall thickening and luminal diameter; reduced TAK1 function was associated with reduced thickness and smaller diameter, whereas activation of TAK1 function was associated with increased thickness and larger diameter. Arterial magnitudes of laminar shear stress (20 dyne/cm 2 ) activated noncanonical TGFβ signaling including TAK1 phosphorylation in mouse endothelial cells. Conclusions: TAK1 is increased in AVF, and TAK1 manipulation in a mouse AVF model regulates AVF thickness and diameter. Targeting noncanonical TGFβ signaling such as TAK1 might be a novel therapeutic approach to improve AVF maturation. Abstract : Supplemental Digital Content is available in the text.